Early Detection And Health Education Initiatives At The Agriculture Office Of Kendari City - Julianti Isma Sari Usma; Desty Triyaswati; Ahmat Rediansyah Putra; Sri Resky Mustafa (Journal Kiara : Nursing and Midwifery, 2026)
Non-Communicable Diseases (NCDs) such as hypertension, diabetes, and overweight often go undetected among employees due to the absence of routine health checks and a heavy workload. This community service program aimed to conduct early detection of NCD risk factors and provide targeted health education for employees of the Fisheries Office of Kendari City. A total of 45 employees participated in health screening activities, including blood pressure measurement, body mass index assessment, and random blood glucose testing, followed by individualized face-to-face health education. The results showed that 49% of participants had hypertension, 46.8% were categorized as overweight, and 92.8% had normal blood glucose levels, with 3.6% classified as prediabetic and 3.6% diabetic. These findings highlight the need for continuous interventions promoting healthy lifestyle behaviors, stress management, and regular health monitoring. This program successfully increased employee awareness of their health status and emphasized the importance of preventing NCDs, contributing to a healthier and more productive work environment.